The potential of a union default to influence the preferences and choices of non-union workers in unionised workplaces. (November 2022) - Harcourt, Mark; Gall, Gregor; Wilson, Margaret; Rubenstein, Korey
This article questions the perception of non-union workers as rather rigid and out-of-reach non-unionists by using research conducted in New Zealand. It explores whether, under new institutional architecture, non-unionists would continue to exhibit the same preferences and exercise the same choices as before. This was done by testing their responses to a union default scenario. The significance of this study concerns how this particular group of workers, contra non-union workers in non-union workplaces, would react to a union default where a union is already available to them. By contrast, non-union workers in non-union workplaces not only at present have effectively no choice for gaining union representation but are also bereft of any experience of it in their workplace. The results suggest 44% of these employees would join as a result of a union default with union density consequently rising in New Zealand from 17–18% to 26–27%.